PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, DAN REPUTASI AUDITOR TERHADAP MANAJEMEN LABA - Afifa Nabila; Daljono Daljono (Diponegoro Journal of Accounting, 2013)
Earnings management is manager effort in manipulating financial report in orderto benefit their self. This behavior is considered as a fraud because it gives a misleadinformation to the financial report user. This research aims to determine and analyze theeffect of independent board commissioner proportion, audit committee, and auditorreputation against the practice of earnings management.The population used in this study were manufacturing companies listed on theStock Exchange during 2008-2010. The sampling technique used in this research waspurposive sampling method and obtained 112 samples. This research used secondary dataof annual report obtained from Indonesia Stock Exchange (IDX) in 2008-2010 period. Theanalysis method that used to analyze the data was the multiple regression.Based on the result of the hypothetical examination in this research, it proved that(1) The independent commissioner proportion does not have a significant effect againstearnings management. (2) Audit committee activity does not have a significant effectagainst earnings management. (3) Audit committee member does not have a significanteffect against earnings management. (4) Auditor reputation significantly has a negativeeffect against earnings management.